O acesso à energia elétrica como manifestação do direito ao mínimo existencial : uma análise com ênfase na dimensão defensiva do direito de acesso à energia elétrica - Rosa, Taís Hemann da (2016)
This study discusses the access to electricity and its connection to the existential minimum. By analyzing the social and constitutional reality in Brazil, it was sought to determine what can be understood as existential minimum and whether the access to electricity should be given as right/integral component of it. Thus, were examined the meaning of the insertion of social rights in the Brazilian constitutional order and the material opening of the catalog of fundamental rights to the existential minimum. The study aimed to delimitate what can be indicated as public services and essential public services of continued provision linked to the existential minimum. The analysis of judgments from Supreme Court of Justice and Federal Supreme Court was conducted, involving the suspension of energy delivery for private individuals and public bodies, as well as data from the Demographic Census of 2010 from the Brazilian Institute of Geography and Statistics about the access to electricity in Brazil. Finally, it is understood that the access to electricity does not constitute an autonomous fundamental right, but a right arising from the existential minimum. The fundamental right that is associated to this access, and, therefore, the fundamental right to be argued, is the right to the existential minimum, this being the fundamental right implied in the Federal Constitution of 1988. Hence, the postulation for the maintenance of the access to electricity can not be ignored when the existential minimum depends on it, be it in the matter of rights for health, education, housing, or any other fundamental right, provided that the link and indispensability of such access to the attainment and/or maintenance of the aforementioned fundamental rights.